(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mouthwash is typically an antiseptic solution used for cleaning the mouth and teeth or for freshening the breath. It is frequently recommended in dentistry to prevent and treat various oral conditions. Recently, the use of natural products, commonly referred to as grandmother remedies, has become widespread. Herbal mouthwashes are in high demand because they effectively target oral pathogens, provide immediate pain relief, and have fewer side effects. Liquid herbal mouthwash can significantly help alleviate bad breath and various oral disorders. These liquids contain anti-inflammatory, antimicrobial, and analgesic properties. In this study, three formulations of herbal mouthwash were developed using spirulina, clove oil, peppermint oil, liquorice, sodium benzoate, salt, and water. Herbal mouthwash includes natural phytochemicals known for their antimicrobial and anti-inflammatory effects. The prepared formulations were further evaluated for color, odor, flavor, pH, and microbial activity using the agar diffusion method.